A laser arrays scan thermography (LAsST) for the rapid inspection of CFRP composite with subsurface defects. (15th October 2019) - Wei, Jiacheng; Wang, Fei; Liu, Junyan; Wang, Yang; He, Lin
Abstract: Laser arrays scan thermography (LAsST) as a nondestructive testing and evaluation (NDT&E) tool is presented to detect the subsurface delamination or abnormally of carbon fiber reinforced polymer (CFRP) composite. A series of woven CFRP specimens with artificial bottom flat holes (BFHs) are prepared for NDT&E by LAsST. The thermal response signal was reconstructed and in turn appeared the analogous thermal responsible behavior similar to pulsed thermography (PT). The thermal response signal was processed by using of Fast Fourier transform (FFT) and principal component analysis (PCA), and FFT amplitude and phase images, PCA image were formed. The signal noise ratios (SNRs) of defects were calculated and employed to evaluate the defect detectability of different post processing algorithms. A likeness optical flow (LOF) approach was proposed to reduce the interruption of lateral thermal diffusion and improve the defect detectability. The experimental results indicate that FFT phase based image shows a relatively high SNR, and the LOF method effectively enlarged the SNRs of defects.